The approximate and exact solutions of the space- and time-fractional Burgers equations with initial conditions by variational iteration method - İnç, Mustafa (Academic Press Inc Elsevier Science, 2008)
In this paper, a scheme is developed to study numerical solution of the space- and time-fractional Burgers equations with initial conditions by the variational iteration method (VIM). The exact and numerical solutions obtained by the variational iteration method are compared with that obtained by Adomian decomposition method (ADM). The results show that the variational iteration method is much easier, more convenient, and more stable and efficient than Adomian decomposition method. Numerical solutions are calculated for the fractional Burgers equation to show the nature of solution as the fractional derivative parameter is changed. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: time- and space-fractional Burgers equations; fractional derivative; variational iteration method; Lagrange multiplier